Pengaruh Saluran Inlet dan Outlet terhadap Thrust dan Kebisingan Mesin Valveless Pulse Jet (Jurnal Inovasi Mesin, 2021)
Unlike common jet engine that had numerous moving components, pulse jet has no moving component. The aim of this study is to examine thrust and noise of valve less pulse jet engine with a volume of combustion chamber 668.66 cm3 , inlet standard size 2.54 cm with a length of 35.56 cm and variations in standard size outlets 2.54 cm, 5.08 cm and 1.52 cm. with air and gas comparison 1: 1 to 1: 6. Basic theories include Cadency effects, acoustics and resonance elements, waves and currents and Lenoir cycles. The material used is stainless steel plate and pipe with a thickness of 0.08 cm. First gas and air fuel are injected in the combustion chamber, spark plugs ignited spark fire and the engine process produces thrust. The thrust on the jet engine occurs because there is a change in the momentum of the gas flowing through the engine. The standard engine produces the highest thrust and noise 0.491 N and 60 dB, variations I 0.588 N and 63 dB, as well as variations II 0.442 N and 60 dB. The variation I is the most perfect engine combustion and the lowest engine temperature.